Dialogs of Performance Art: Nature and Practice from what is Lived (Mayéutica Revista Científica de Humanidades y Artes, 2014)
Social anthropology has studied meanings, which are taken by the body in traditional cultures to construct, from science, a concept related to contemporary body. Interdisciplinary investigations define a particular tension between our biological origins and our human originalities (Masiá). The body acts and communicates; it is about performance art which assumes language, technology, freedom or love inside human originalities which necessarily depend on his corporal and biological origins. Performance Art starts demonstrating its sense of incorporation to an individual territory which happens to become collective along with other bodies that share its daily space. Performance art is understood taking into account the relationship between “to have” - the biological thing - and “to be” - the spiritual thing-. That is why, in the quest for corporal significances and the study of the body, an experience from performance art workshops “ Brace Tirro “ (Pineda) has been adopted to describe a body that connects to what is outside through an “understanding self”. From this point on, dialogs of performance art are constructed through the resignificance of “the self” of a group of persons who communicate with their body, the analysis of their representation and performing in a common space. Their bodies are affected by questions which tell of a moving body in an invaded space, of an individual body in a collective subject, and of a body language in a visual speech, it’s about art interpretation.
Keywords: anthropology; space; art; body; performance